METHODS FOR SOLVING PROBLEMATIC SITUATIONS IN HIGHER EDUCATION MANAGEMENT (American Journal of Interdisciplinary Research and Development, 2025)
Higher education institutions are pivotal in advancing society's scientific, cultural, and economic progress. They not only equip students with contemporary knowledge but also contribute to the dissemination of progressive ideas and societal values. Nonetheless, the management of higher education faces a variety of internal and external challenges. Addressing these issues demands the adoption of contemporary management approaches and strategies, which are vital for enhancing the overall system.